From the Theory of the Firm to FDI and Internalisation: A Survey - Valeria Gattai (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper surveys recent contributions on the Internalisation issue, based on different theories of the firm, to show how the make-or-buy decision, at an international level, has been assessed through the opening up of the black box - traditionally explored by the theorists of the firm and the simultaneous endogenization of the market environment as in the International Economics tradition. In particular, we consider three Archetypes Grossman-Hart-Moore treatment of hold-up and contractual incompleteness, Holmstrom-Milgrom view of the firm as an incentive system, Aghion-Tirole conceptualisation of formal and real authority in organisations and show how they have been embedded in industry and general equilibrium models of FDI to explain the boundaries of global firms.
Keywords: F1; F2; L1; L2; 330; FDI; Internalisation; International Economics; Incomplete contracts; Globalisierung; Direktinvestition; Outsourcing; Theorie der Unternehmung